Workers Adaptation during Pandemic, Evidence from Bali Province as Main Tourist Destination in Indonesia - Agni Alam Awirya; Dian Novita; Christina Irawadi; Regina Niken Wilantari (UPT Penerbitan Universitas Jember, 2022)
The COVID-19 pandemic has had a major impact on various sectors in Indonesia, one of which is the tourism sector. This stems from the policies carried out by the government in the form of travel bans to closing hotels which have reduced the supply and demand of domestic and international tourism which has led to the stagnation of the tourism industry. As a result, many workers in the tourism sector are affected, ranging from layoffs to reduced income. This study aims to find out how the impact and adaptation of the tourism sector workforce during the COVID-19 pandemic was extended to the analysis of labor migration in the tourism sector affected by the COVID-19 pandemic using SAKERNAS data in August 2020 and survey data on labor conditions. The results of the study show that the COVID-19 pandemic has had a huge impact on tourism sector employment in the form of layoffs, changes in types of work to a decrease in income. Various alternatives in doing business to increase additional income or in the field of work have been carried out by workers as an adaptation step to new conditions during the COVID-19 pandemic.